Fostering Innovation for Productivity and Competitiveness - World Bank (Washington, DC, 2014)
This note provides a medium-term agenda for supporting Mexico's competitiveness by fostering greater innovation. Globalization and the dynamism of economies that compete with Mexico, particularly those in East Asia, bring a renewed urgency to Mexico's innovation policy agenda. While the firm is at the center of innovation, empirical evidence shows that public policy can generate an external environment more conducive to innovation. The past decade has brought several policy changes and new programs, but further changes will help the country catch up with more innovative economies and move up the value chain. Given the multi sectoral nature of innovation and multiplicity of programs, better coordination in policymaking, stronger mechanisms to define budgetary priorities for innovation, and greater coherence and synergies among public policy interventions are necessary. A comprehensive innovation strategy as used in highly innovative economies such as Finland can help guide such efforts.